EphH, a unique epoxide hydrolase encoded by Rv3338 is involved in the survival of Mycobacterium tuberculosis under in vitro stress and vacuolar pH-induced changes - Garg, Tanu; Das, Swetarka; Singh, Shriya; Imran, Mohmmad; Mukhopadhyay, Atri; Gupta, Umesh D.; Chopra, Sidharth; Dasgupta, Arunava (Frontiers in Microbiology, 2023)
Mycobacterium tuberculosis (Mtb), one of the deadliest pathogens,, has evolved with different strategies of survival inside the host, leading to a chronic state of infection. Phagosomally residing Mtb encounters a variety of stresses, including increasing acidic pH. Previous studies reported various Mtb genes exhibited altered expression profiles while encountering acidic pH. To better understand the host-pathogen interaction, it is imperative to identify the role of various genes involved in the survivability of Mtb during acidic pH environment. In this context, the present work describes the characterization of the Mtb gene, Rv3338, which was previously known to be associated with the aprABC locus induced while encountering acidic stress within the macrophage. Bioinformatic analysis showed its similarity to epoxide hydrolase (EH), which is confirmed by enzymatic assays and, thus, renamed EphH. Subsequently, we have deciphered its indispensable role for Mtb in protection from acidic stress by using the CRISPRi knockdown strategy. Our data established the involvement of EphH in response to phagosomal acidification inside macrophages. Our Findings also demonstrated the pH dependent role of EphH for the survival of Mtb during nutrient starvation and in conferring resistance against elevated endogenous ROS levels during stress environment. To the best of our knowledge, this is the first report of an EH of Mtb as a crucial protein for bacterial fitness inside the host, the phenomenon central to its pathogenesis.